The Science of Open Spaces - Curtin, Charles. (Island Press/Center for Resource Economics : Imprint: Island Press, 2015)
This publication proposes that we return to “first principles”--fundamental physical laws of the universe--and think about complex systems from the ground up based on modern scientific theory backed up by practical experience.  Since the days of the American Frontier, our management policies have promoted a one-size-fits-all mentality for large, complex landscapes. Landscape ecologist Charles Curtin argues that instead we need a science-based approach that accounts for the dynamic nature of complex systems and gives local stakeholders a say in their futures. Curtin walks us through foundational concepts of thermodynamics, ecology, sociology, and resilience theory, applying them to real-world examples from years he has spent designing large-scale, place-based collaborative research programs in the United States and around the world.